Dinamika Temperatur Permukaan Tanah di Kota Pariaman Berdasarkan Citra Satelit - Ridho Illahi; Fajrin Fajrin; Ilham Armi; Dwi Marsiska Driptufany; Defwaldi Defwaldi (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Changes in land surface temperature are one of the important indicators in monitoring global environmental change. In the last decade, increasing surface temperatures have become a global concern, as they have the potential to affect ecosystems, air quality, water availability and human health. In addition, increasing land surface temperature also has a direct impact on the urban heat island phenomenon, which can worsen environmental conditions in urban areas. In this context, analyzing periodic changes in land surface temperature is important to understand the patterns and factors that influence these changes. The objectives in conducting this research, namely: Analyzing the land surface temperature, Creating a regional land surface temperature map and Analyzing changes in land surface temperature from the land surface temperature map of Pariaman City in 2015, 2019, and 2023. Based on the results of the analysis of changes in land surface temperature using Landsat 8 OLI/TIRS images in 2015, 2019, and 2023, it was found that there were significant variations in temperature changes in several areas. Landsat 8 image data is processed through several stages, starting from converting Digital Number (DN) values to spectral radians, brightness temperature, to estimating Land Surface Temperature (LST) in Celsius units. The analysis shows that there was a significant increase in land surface temperature during the period, especially in urban and coastal areas. In 2015, the majority of areas had temperatures of 20°C-24°C, while in 2019 it shifted to 24°C-28°C, and in 2023 it was dominated by temperatures of 28°C-32°C and above 32°C. These changes reflect a significant local warming trend, influenced by human activities and land use change. This research is expected to contribute to the understanding of environmental dynamics and support spatial planning that is more adaptive to climate change.